Gender wage discrimination by distribution of income in Mexico, 2005-2020 - Miguel Ángel Mendoza González (Latin American Economic Review, 2020)
This paper aims to analyze the hourly gender wage gap between men and women in Mexico for the period 2005-2020. To this end, a number of variables is selected to reflect workers' human capital, household circumstances and workplace characteristics; then, a novel non-parametric method decomposes wage differentials between men and women into its composition and structure effects throughout the distribution of labor income. Results are consistent with the sticky-floor hypothesis, where male workers earn higher hourly wages than female workers at low income levels. However, differentials decrease in the upper part of the distribution and may even reverse, favoring women over men at the highest income levels.
Keywords: C14; J16; J24; J31; J71; O54; 330; income distribution; gender wage gap; gender wage discrimination; non-parametric methods; sticky floors